Recurrent chest pain as a rare presentation of extra‐pelvic endometriosis - Mousa Hussein; Mutaz Albakri; Shanima Ismail; Abbas Alabbas; Samir Al Hyassat (Clinical Case Reports, 2021)
Abstract Periodic chest pain, with bloody pleural effusion should raise the suspicion of pleural endometriosis as a well‐known, but a rare condition in clinical practice.